Modélisation des niveaux marins extrêmes associés à la circulation des cyclones Lenny (1999) et Omar (2008), commune de saint-pierre, littoral nord-ouest de la Martinique - Alexandre Nicolae Lerma (Éditions en environnement VertigO, 2015)
Coastal floods are commonly associated to meteorological local storm conditions and well-known storm surge phenomenon resulting from both reversed barometric effect and wind driven setup. The wave breaking plays a major role too in water level variation on the beach. It causes two kinds of water level changes: a static component called wave setup and an instantaneous one called swash or uprush. Those to phenomenon are responsible in certain case for more than 2/3 of total level rises above mean sea level. During Lenny and Omar hurricane circulation, the Martinique island west coast was considerably affected. Water levels reached during the two hurricanes circulation was reconstituted (hindcasting method) for North West Coast of de island, particularly for the district of St Pierre. Variation factors was decomposed and modeled with nesting method using ADCIRC hydrodynamic model for tide and meteorological surge. The propagation model SWAN and breaking wave model pCOULWAVE, was used to estimate wave setup and swash components. This work about decomposition of sea water variation level associated to reconstitution of floods limits by field inquest and evidences, point up the district vulnerability in front of strong hurricane swell. It also shows the necessity to consider all sea level variation factors in flood risk studies in terms of preventive documents and actions.